2015
DOI: 10.1002/jpln.201400587
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of glycine uptake by pak choi in organic and conventional soil under different glycine concentrations: A pot study

Abstract: Many studies have shown that plants can utilize organic N in the form of amino acids. However, it is unclear whether the glycine-uptake capability responds differently to various farm management systems, and whether the interaction of farm management type with soil glycine concentrations affects the glycine uptake by plants. A pot experiment was conducted in which pak choi (Brassica campestris ssp. chinensis Makino var. communis Tsen et Lee) was grown in soil from organic and conventional agricultural systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(60 reference statements)
1
2
0
Order By: Relevance
“…Plants are able to take up amino acids as a source of N [ 3 , 52 ], and we confirmed Gly was absorbed by pak choi seedlings (Figs 3 , 4 and 6 ). For pak choi grown in mixtures of Gly and NO 3 - -N, 15 N-Gly uptake accounted for 28.2–35.7% of shoot N and 53.3–61.7% of root N ( Fig 3B and 3D ).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Plants are able to take up amino acids as a source of N [ 3 , 52 ], and we confirmed Gly was absorbed by pak choi seedlings (Figs 3 , 4 and 6 ). For pak choi grown in mixtures of Gly and NO 3 - -N, 15 N-Gly uptake accounted for 28.2–35.7% of shoot N and 53.3–61.7% of root N ( Fig 3B and 3D ).…”
Section: Discussionsupporting
confidence: 65%
“…NO 3 - -N has been traditionally viewed as the main form of inorganic N taken up by plants. However, an increasing number of studies have shown that organic N also contributes to plant N nutrition [ 3 7 ]. Amino acids are ubiquitously found in the soil solution and may represent a significant source of N for plants in terrestrial ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to advances in technology, it has been revealed that plants cannot only absorb inorganic N but also a certain amount of small molecule organic-N (Wang et al, 2015). Inorganic N sources include nitrate, ammonium, amino acids, small molecular-weight peptides, and proteins, all of which are important N sources provided by fertilizers (Gioseffi et al, 2011;Paungfoo-Lonhienne et al, 2012).…”
Section: Introductionmentioning
confidence: 99%